IFPRI Strategy Refresh 2018-2020 - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
In 2012, IFPRI developed its 2013–2018 strategy to address unprecedented challenges in the food policy landscape. Five years later, many of those challenges persist while new threats and opportunities have arisen that will have fundamental impacts on future food security and nutrition. The Institute is refreshing its strategy to respond to these ongoing and emerging issues while continuing to deliver on its mission to provide researchbased policy solutions that sustainably reduce poverty and end hunger and malnutrition. IFPRI’s vision remains that of a world free of hunger and malnutrition. The IFPRI Strategy Refresh: 2018–2020 outlines the strategic direction of the Institute for the next three years. It reviews the changing landscape of global developments as well as persistent issues that influence food policy. It also presents updates to IFPRI’s research areas that will drive the Institute’s efforts to reshape food systems and contribute to the achievement of the Sustainable Development Goals (SDGs). Partnerships, communications, capacity strengthening, and data and knowledge management will continue to be essential components for taking IFPRI’s research from action to impact. The strategy refresh was informed by consultations with IFPRI staff and trustees as well as by feedback from IFPRI’s partners and collaborators.